2020
DOI: 10.1186/s12935-020-01500-8
|View full text |Cite
|
Sign up to set email alerts
|

XIST lost induces ovarian cancer stem cells to acquire taxol resistance via a KMT2C-dependent way

Abstract: Background/aims: The expression levels of long non-coding RNA XIST are significantly associated with paclitaxel (Pac) sensitivity in ovarian cancer, but the mechanism of action remains unclear. Therefore, this experimental design was based on lncRNA XIST analysis to regulate the effect of XIST on the tumor stem cell and paclitaxel sensitivity in ovarian cancer. Methods: Sphere assay and fluorescence activated cell sorting (FACS) were used to determine the expression levels of XIST and sensitivity to paclitaxel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“… 152 In addition, XIST expression correlates with ovarian cancer development, with downregulation in advanced stages, and higher expression is associated with better prognoses. 152 In ovarian cancer cell lines, XIST overexpression suppresses cell proliferation, 153 , 154 , 155 while XIST knockdown has the opposite effect. 153 XIST suppresses cancer progression through sponging hsa-miR-214-3p 154 and miR-106a.…”
Section: Xist and Sex-biased Diseasesmentioning
confidence: 99%
“… 152 In addition, XIST expression correlates with ovarian cancer development, with downregulation in advanced stages, and higher expression is associated with better prognoses. 152 In ovarian cancer cell lines, XIST overexpression suppresses cell proliferation, 153 , 154 , 155 while XIST knockdown has the opposite effect. 153 XIST suppresses cancer progression through sponging hsa-miR-214-3p 154 and miR-106a.…”
Section: Xist and Sex-biased Diseasesmentioning
confidence: 99%
“…The X-chromosome inactivating specific transcript ( XIST ) gene is localised in the X-chromosome inactivation centre (Xic), encodes for the XIST lncRNA, and is associated with tumour regulation in various malignancies. In ovarian cancer, XIST promotes the stability of lysine (K)-specific methyltransferase 2C (KMT2C) mRNA, thereby indirectly promoting histone H3 methylation at lysine 4 and hence decreasing CSC proliferation [ 145 ]. XIST can also alter the phenotype of CSCs by increasing paclitaxel sensitivity in patients; miR-93-5p can reverse this pathway, demonstrating multifaceted interactions between epigenetics and lncRNAs [ 145 ].…”
Section: Long Noncoding Rnas and Cancer Stem Cellsmentioning
confidence: 99%
“…Several studies have implicated lncRNAs in cancer drug resistance and recent findings showed that lncRNAs can modulate treatment-resistant phenotypes via regulation of CSC biology and function [ 145 , 155 , 156 ].…”
Section: Long Noncoding Rnas and Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of HIFs after hypoxia can directly or indirectly stimulate the maintenance of stemness markers, such as OCT4, SOX2, etc ( Zaarour et al, 2021 ). LncRNA XIST can increase the sensitivity of breast CSCs to chemotherapy drugs by regulating KMT2C ( Huang et al, 2020 ). In liver cancer, lncRNA HDAC2 promotes the proliferation and self-renewal of liver CSCs by activating the Hedgehog signaling pathway ( Wu J. et al, 2019 ).…”
Section: Lncrnas Emerge As New Epigenetic Regulators Of Mitophagy In Cancersmentioning
confidence: 99%